An analysis of the validity of self reported occupational histories using a cohort of workers exposed to PCBs. Issue 10 (October 1987) - Rosenberg, C R; Mulvihill, M N; Fischbein, A; Blum, S
Abstract : An investigation was conducted to examine the validity of self reported work histories obtained from a sample of 326 capacitor manufacturing workers who had participated in an epidemiological study relating health abnormalities to exposure to polychlorinated biphenyls. Based on objective personnel records obtained for 288 members of the sample group, validity scores ranged from 20% to 100% with most falling between 70% and 75%. This validity range corresponded to misclassification proportions ranging from 13% to 29%. Exposure misclassification tended to be random for men but non-random for women (overestimation of exposure). By means of multiple regression analysis, the diversity of the job categorical pattern was found to be a significant independent predictor of validity. The factors sex, duration, and time lapse were also significant validity predictors but only interactively with job diversity. There were also indications that interviewer skill could be an important factor. Knowledge of the magnitude of these factor effects could be critical in planning retrospective epidemiological studies.